Structural resolution of inorganic nanotubes with complex stoichiometry - Geoffrey Monet (Nature Portfolio, 2018)
Structural determination of inorganic nanotubes has lagged far behind that of their carbon-based counterparts. Here, the authors present a transferable methodology, combining wide angle X-ray scattering and computation, to quantitatively resolve the atomic structure of inorganic nanotubes with complex stoichiometry.